2017
DOI: 10.1177/0954411916687338
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity vibrations normalize adipogenesis-induced morphological and molecular changes of adult mesenchymal stem cells

Abstract: Bone marrow mesenchymal stem cells that are committed to adipogenesis were exposed daily to high-frequency low-intensity mechanical vibrations to understand molecular, morphological and ultrastructural adaptations to mechanical signals during adipogenesis. D1-ORL-UVA mouse bone marrow mesenchymal stem cells were cultured with either growth or adipogenic medium for 1 week. Low-intensity vibration signals (15 min/day, 90 Hz, 0.1 g) were applied to one group of adipogenic cells, while the other adipogenic group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…To elucidate the effects of vibration, the cells were subjected to a specific vibration regime; however, loading parameters and time schedules varied among the studies (Table 1), but were within the range of 20-90 Hz and <1 g magnitude. It was demonstrated by the majority of studies, that LMHFV induced the expression (Marycz et al, 2016;Baskan et al, 2017). This finding appears to be consistent regardless of the MSC origin or the vibration setting or duration.…”
Section: Mscssupporting
confidence: 59%
“…To elucidate the effects of vibration, the cells were subjected to a specific vibration regime; however, loading parameters and time schedules varied among the studies (Table 1), but were within the range of 20-90 Hz and <1 g magnitude. It was demonstrated by the majority of studies, that LMHFV induced the expression (Marycz et al, 2016;Baskan et al, 2017). This finding appears to be consistent regardless of the MSC origin or the vibration setting or duration.…”
Section: Mscssupporting
confidence: 59%
“…In vitro studies have also been conducted to illustrate the effect of vibration on MSCs differentiation and the underlying molecular mechanism. Ozcivici’s group found that 1-week treatment (15 min/day) of LMHF (0.15 g, 90 Hz) vibration promoted osteoblastic differentiation and suppressed adipogenic differentiation of mouse BM-MSCs, showing a significant increase of runx2 and reduction of PPARγ and C/EBPα [ 89 , 90 ]. Chen et al also reported that 0.3 g acoustic vibration at 800 Hz (30 min/day) promoted osteogenic differentiation and suppressed adipogenic differentiation via upregulating runx2 expression and downregulating PPARγ [ 91 ].…”
Section: The Molecular Mechanisms Regulating Osteoblast and Adipocmentioning
confidence: 99%
“…The exact mechanism underlying the vibration-induced differentiation is not yet clear, and further studies are required to explore this molecular phenomenon [78]. Low-intensity vibration leads to the disruption of actin fibers, which favors adipogenesis in MSC differentiation; however, the exact mechanism is not yet clear [79]. An ultrasound-based method, acoustic tweezing cytometry, also facilitates the formation and contractility of F-actin, which ultimately promotes Yes-associated protein (YAP) translocation, thereby favoring osteogenesis [80].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 99%